2011
DOI: 10.1016/j.mad.2011.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor binding protein-6 delays replicative senescence of human fibroblasts

Abstract: Highlights► Proteomic analysis of senescent secretome reveals upregulation of IGFBP-6 in fibroblasts. ► IGFBP-6 knockdown induces premature senescence in young fibroblasts. ► IGFBP-6 lentiviral overexpression delays replicative senescence in fibroblasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 66 publications
1
30
0
Order By: Relevance
“…Osteoprotegerin could regulate bone resorption, modeling, and remodeling, which is mainly secreted by osteoblasts [41, 42]. Meanwhile, IGFBP-6 could control the differentiation of cells and prevent the apoptosis and aging of human fibroblasts [43, 44]. IL-8, a chemokine of the immune system, could recruit neutrophils, endothelial cells, and macrophages to sites of injured tissues [45, 46].…”
Section: Discussionmentioning
confidence: 99%
“…Osteoprotegerin could regulate bone resorption, modeling, and remodeling, which is mainly secreted by osteoblasts [41, 42]. Meanwhile, IGFBP-6 could control the differentiation of cells and prevent the apoptosis and aging of human fibroblasts [43, 44]. IL-8, a chemokine of the immune system, could recruit neutrophils, endothelial cells, and macrophages to sites of injured tissues [45, 46].…”
Section: Discussionmentioning
confidence: 99%
“…(54,94,95). By contrast, IGFBP6 expression is associated with delayed replicative senescence of HDF (96). Our previous study of gene expression profiles during replicative senescence also demonstrated that IGFBP4 and IGFBP6 were downregulated, whereas IGFBP2, IGFBP3, IGFBP5, and IGFBP7 were upregulated (25), supporting their different contributions to senescence and the aging progress.…”
Section: Expression Of Sasp Regulatory Factorsmentioning
confidence: 66%
“…Therefore, elevated levels of Scx in PAI-1 knockout hearts may contribute to cardiac fibrogenesis; ii) IGFBP6 (Insulin like growth factor binding protein 6), a 29 kDa modulator of IGF activity, induces cellular proliferation, suppresses apoptosis and delays cellular senescence. IGFBP6 may be involved in liver fibrogenesis [50], [51] indicating elevated IGFBP6 in PAI-1 knockout hearts may play a role in cardiac-selective fibrogenesis; iii) Klf6, a 31 kDa zinc finger transcription factor, regulates TGF-β gene expression and is associated with fibrosis in non-alcoholic fatty liver diseases. Klf6 is also involved in oxidative stress-induced stellate cell activation, inflammation and increased collagen synthesis [52][54].…”
Section: Discussionmentioning
confidence: 99%